Liquidity, risk and the global transmission of the 2007-08 financial crisis and the 2010-2011 sovereign debt crisis - Alexander Chudik; Marcel Fratzscher (European Central Bank (ECB), 2012)
The paper analyses the transmission of liquidity shocks and risk shocks to global financial markets. Using a Global VAR methodology, the findings reveal fundamental differences in the transmission strength and pattern between the 2007-08 financial crisis and the 2010-11 sovereign debt crisis. Unlike in the former crisis, emerging market economies have become much more resilient to adverse shocks in 2010-11. Moreover, a flight-to-safety phenomenon across asset classes has become particularly strong during the 2010-11 sovereign debt crisis, with risk shocks driving down bond yields in key advanced economies. The paper relates this evolving transmission pattern to portfolio choice decisions by investors and finds that countries' sovereign rating, quality of institutions and their financial exposure are determinants of cross-country differences in the transmission.
Keywords: E44; F3; C5; 330; advanced economies; Capital flows; Emerging market economies; global financial crisis; high dimensional VARs; liquidity; risk; sovereign debt crisis; transmission